An Informal Report to the Kansas Legislature, January 2011 - Pierzynski, Gary M. (My University, 2011)
This informal report to the Kansas Legislature summarizes the wide-ranging impact of K-State Research and Extension in 2011, highlighting initiatives in agriculture, environmental stewardship, public health, and community development across Kansas.
UNN25_2011_01
Keywords: UNN25; Administrative and Research Reports; legislature